The legacy of 1 Enoch on Ethiopian literature - Asale, Bruk Ayele (Journal for semitics, 2014)
1 Enoch disappeared centuries ago from the Jewish and the Christian world where it originated, and from where it spread widely gaining canonical authority. It survives in its entirety in the Ethiopian Orthodox Tewhahedo Church (EOTC) to date. Hence, it is to be expected that traces of the book's legacy can still be detected in the church. Evidently, the book has attracted a great deal of scholarly attention in the last hundred years, more specifically since the landmark discoveries of the Dead Sea Scrolls. However, its legacy in the EOTC and its influence on the community that is credited with honouring it for many centuries, keeping its original authority and usage intact, have been largely omitted from the discussion. This article, therefore, asks what traces the influence of 1 Enoch has left in Ethiopia and in what its legacy consists. In its attempt to respond to these questions, the article focuses particularly on the literary influences the book has on Ethiopian literature. Though the influence and legacy of the book is not limited to the literary realm, the article limits itself to it alone. Subsequent discussions may go beyond this to consider ways in which the book may have contributed to the making of Ethiopia at large.